The craft of poetry : a primer in verse - Newlyn, Lucy (Yale University Press, 2021)
"A wonderfully accessible handbook to the art of writing and reading poetry--itself written entirely in verse. How does poetry work? What should readers notice and look out for? Poet Lucy Newlyn demystifies the principles of the form, effortlessly illustrating key approaches and terms--all through her own original verse. Each poem exemplifies an aspect of poetic craft--but read together they suggest how poetry can evoke a whole community and its way of life in myriad ways. In a series of beautiful meditations, Newlyn guides the reader through key aspects of poetry, from sonnets and haiku to volta and synecdoche. Avoiding glosses and notes, her poems are allowed to speak for themselves, and show that there are no limits to what poetry can communicate. Newlyn's timeless verse will appeal to lovers of poetry as well as to practitioners, teachers, and students of all ages.--